2001
DOI: 10.1016/s0304-3959(01)00349-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical importance of changes in chronic pain intensity measured on an 11-point numerical pain rating scale

Abstract: Pain intensity is frequently measured on an 11-point pain intensity numerical rating scale (PI-NRS), where 0=no pain and 10=worst possible pain. However, it is difficult to interpret the clinical importance of changes from baseline on this scale (such as a 1- or 2-point change). To date, there are no data driven estimates for clinically important differences in pain intensity scales used for chronic pain studies. We have estimated a clinically important difference on this scale by relating it to global assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

107
3,322
22
63

Year Published

2003
2003
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 4,552 publications
(3,514 citation statements)
references
References 19 publications
107
3,322
22
63
Order By: Relevance
“…However, the minimal end point to efficacy has been found to be a decrease in pain intensity of at least 433%, 15 min after the study medications. This level of change in pain intensity has been best associated with clinically important differences by patients (Farrar et al, 2001). As expected, OTFC has been found to be more effective and rapid than oral morphine for treating breakthrough pain, producing a 433% change in about 42% of patients within 15 min after administration (about 32%) (Coluzzi et al, 2001).…”
Section: Intravenous Morphine and Otfc Doses S Mercadante Et Almentioning
confidence: 63%
“…However, the minimal end point to efficacy has been found to be a decrease in pain intensity of at least 433%, 15 min after the study medications. This level of change in pain intensity has been best associated with clinically important differences by patients (Farrar et al, 2001). As expected, OTFC has been found to be more effective and rapid than oral morphine for treating breakthrough pain, producing a 433% change in about 42% of patients within 15 min after administration (about 32%) (Coluzzi et al, 2001).…”
Section: Intravenous Morphine and Otfc Doses S Mercadante Et Almentioning
confidence: 63%
“…However it should be noted that VAS scores for pain intensity were measured once a day at a fixed time, reflecting the pain intensity at that particular moment, whereas patients' opinions about treatment result should include all improvements experienced by the patient during the whole treatment period. Interestingly, for patients satisfied with treatment results and willing to continue treatment, the mean pain reduction was 28.5%, a clinically important difference [25], whereas for patients not willing to continue treatment there was no improvement in pain intensity during the treatment period as compared to the baseline period. Regarding the accuracy of pain integration into this assessment, it is interesting to note that Coghill et al [26] found that individuals with similar activation patterns of the somatosensory, the anterior cingulate and prefrontal cortex provided similar subjective reports of pain magnitude.…”
Section: Differences Regarding Outcomesmentioning
confidence: 94%
“…Patients had PNP due to post‐herpetic neuralgia (PHN) (pain persisting for at least 6 months since shingles vesicle crusting), post‐traumatic nerve injury (PNI) (minimum of 3 months) or non‐diabetic painful peripheral polyneuropathy (minimum of 3 months), and had an average numeric pain rating scale (NPRS) (Farrar et al., 2001) score ≄4 over a period of at least 4 consecutive days. Patients had to be naĂŻve to treatment with the capsaicin 8% patch and either naĂŻve to treatment with pregabalin and gabapentin, or, in the opinion of the investigator, had not received adequate treatment with pregabalin or gabapentin (Dworkin et al., 2005).…”
Section: Methodsmentioning
confidence: 99%